High lactic acid production by Lactobacillus sp. V156 isolated from Vietnamese fermented mustard green - Thuoc, Doan Van; Huong, Pham Thi; Phong, Tran Huu (Vietnam Journal of Science and Technology, 2021)
In the present study, a lactic acid producing bacterium was isolated and screened from fermented mustard green. The selected bacterial strain (V156) was classified into genus Lactobacillus. High lactic acid concentration of 101.6 g/L and productivity of 2.82 g/L/h were efficiently achieved by Lactobacillus sp. V156 after 36 h of cultivation in fed-batch fermentation using ammonium hydroxide as the neutralizing agent. The production of high lactic acid in short cultivation time demonstrates that Lactobacillus sp. V156 is a promising strain for L-lactic acid production